DAMPAK PARIWISATA PULAU BAWAH TERHADAP SOSIAL EKONOMIMASYARAKAT KABUPATEN KEPULAUANANAMBAS - Garda Putra Megantara (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
This study identifies the impact that has caused on the socio-economic community around the existence of a new tourism island of Bawah which is located in Anambas Islands Regency, Riau Islands Province. This research was carried out because tourism was fully managed by foreign phak and there were foreign tourists who began to appear in the community environment. This type of research uses a descriptive qualitative approach, where data collection is obtained from the results of previous studies in several journals and other online websites. the purpose of this study is to analyze the impacts that occur with the existence of tourism activities that are caused by the development and development of Pulau Bawah tourism. The results of the study indicate that there have been some very significant changes with the existence of this island tourism based on the scope or boundary that was made a reference by researchers